Network strategy - Baum, Joel A. C.; Rowley, Timothy J. (Emerald, 2008)
Research at the intersection of social networks and strategic management identifies a range of performance-enhancing network position advantages - access to partners, information, innovation, and resources - that are distributed differentially across network positions. While research indicates how network positions can be used to advantage, it says little about how these positions are established, sustained, and destroyed, and so we know little about the role of actors' strategic goals and self-interests in shaping network structures.Volume 25 of Advances in Strategic Management aims to inspire a shift from discussions of network effects to network processes. Each chapter contributes to the crafting of a more dynamic view that increases our understanding of the origins, evolution and decay of network structures, positions and their associated advantages.